1999
DOI: 10.1097/00007632-199907150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Scoliosis Research Society Instrument for Evaluation of Surgical Outcome in Adolescent Idiopathic Scoliosis

Abstract: This questionnaire addresses patient measures for evaluation of outcome in adolescent idiopathic scoliosis surgery by examining several domains. It also allows for dynamic monitoring of scoliosis patients as they become adults. This is a validated instrument with good reliability measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
258
0
9

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 426 publications
(268 citation statements)
references
References 22 publications
1
258
0
9
Order By: Relevance
“…Most of the long-term results in the literature are with the Harrington rod system [23,24,32,47]. Williers et al reported 40% final correction rate in a 10.8 years follow-up study [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the long-term results in the literature are with the Harrington rod system [23,24,32,47]. Williers et al reported 40% final correction rate in a 10.8 years follow-up study [47].…”
Section: Discussionmentioning
confidence: 99%
“…These studies also report that Harrington rod system has comparable clinical and radiological results with the modern instrumentation systems, however, the final deformitycorrection rates are very small and the overall lifequality at the last follow-up visit is almost unchanged when compared with the third-generation instrumentation systems [17,21,23,24,26,31,32,47]. Long-term results with the modern systems are limited [5,21,23,26,29,33]. It is reported that there is a 7°-17°correction loss in 5-15 years follow-up, but the vertebral stability is maintained and almost no correction loss is observed after two postoperative years [23,29,33,34].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Haher et al [14] designed the Scoliosis Research Society (SRS) Outcome Instrument, which is a simple, disease-specific, patient-based assessment. Modifications of this instrument resulted in the SRS-22 Patient Questionnaire that covers the domains of function/activity, pain, self-image/appearance, mental health and satisfaction with management.…”
mentioning
confidence: 99%
“…New questionnaires have been developed [2,7,29] and are currently being evaluated [29]. A number of previous studies have discussed quality of life (QL) in general terms [12,17,21,34].…”
mentioning
confidence: 99%